PERBEDAAN HASIL BELAJAR MAHASISWA YANG BEKERJA DENGAN TIDAK BEKERJA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP - 34-42 . Hadi Purwanto (CIVED, 2013)
The background ofthe problem is the economic factors make college students take the part time job beside studying,thuscausing the students achieved the low grades and they could not takes their credit well. This research isaimed todetermine the relationship between students’learning activitieswithstudents learning achievement sand also the differences between the students’ achievements for the ones who take the part time job and who do not in EducationalProgram of Building Engineering,Department of Civil Engineering,Faculty of Engineering,State University ofPadang. The population was 277Students ofEducationalProgramBuilding Engineering. The sampling technique was taken by using proportionalrandom sampling. Techniquesof data collectionwas the questionnairesanddocumentation. The results ofthis study showed at the95% confidence level and itindicates that thereis a significant relation ship between learning activitieswith the students’learning achievements. Furthermore, theexaminationof the results oft-test analysisobtained Tcount=4.449>Ttable=1.645.Ho is rejectedand. Ha is accepted which means that there aresignificantdifferences between the working students and those who is not working. The working students achieved the better grade than the ones who is not working. Key words :        college student, activities, achievement